The impact of audit market concentration on audit quality: evidence from Indonesia - Mutiara Clarina,; Fitriany Fitriany, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examines the impact of audit market concentration on audit quality when regulation about mandatory audit firm rotation are applied in Indonesia. This study used 2,578 firm-years of data from nonfinancial companies listed on the Indonesia Stock Exchange (IDX) during 2008–2015. Audit quality was measured by discretionary accruals and abnormal working capital, and market concentration was calculated by the Herfindahl–Hirschman Index. The study found that market concentration decrease the accrual discreationer and improves audit quality. This outcome is likely because auditors experience in a particular industry have a better understanding of industry risk and will thus undertake better audit planning and procedures that tend to improve audit quality. So, regulators need to encourage public accounting firms to specialise in specific areas and have better knowledge of the industry to make audit quality better.